2021
DOI: 10.2147/jaa.s318104
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase March1 Facilitates OX40L Expression in Allergen-Stimulated Dendritic Cells Through Mediating the Ubiquitination of HDAC11

Abstract: Background: It was demonstrated that membrane-associated RING-CH 1 (March 1) might play an important role in the pathogenesis of asthma. Methods: The levels of mRNA and protein were measured by qRT-PCR and Western blot, respectively. Immunofluorescence assay was used to determine whether March1 co-locates with HDAC11. Co-immunoprecipitation was performed to examine the combination of proteins. Moreover, luciferase assay was used to measure the promoter activity of genes. Results: The mRNA and protein levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Rs reduced the IL-10 expression in DCs. MARCH1 is an E3 ligase, which can induce ubiquitination in targeted proteins to induce the protein degradation 17 . Thus, immunoprecipitation (IP) was performed with protein extracts of DC using an anti-MARCH1 Ab as a bait.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rs reduced the IL-10 expression in DCs. MARCH1 is an E3 ligase, which can induce ubiquitination in targeted proteins to induce the protein degradation 17 . Thus, immunoprecipitation (IP) was performed with protein extracts of DC using an anti-MARCH1 Ab as a bait.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the indication that Rs increases cortisol release, we found that cortisol was associated with the increased MARCH1 expression in DCs of the mice exposed to Rs. MARCH1 is an E3 ligase and can help target protein breakdown 17 . Recent studies have also shown that MARCH1 interferes with immune regulatory functions, particularly by favoring Th2 polarization 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have also identified the ubiquitination as a central process in the pathogenesis and development of asthma [ 23 , 25 ]. Ubiquitination also indirectly participated in the pathogenesis of asthma through regulating functions of macrophage and dendritic cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%